The Manifestation of Unconscious Mind in Liana Flores’ Rises The Moon - Dermawan, Zahwa Amelia Putri; Soenarko, Zahra Pramatatya; Pratiwi, Astika R.; Napitupulu, Johanes Claudio Perdana; Pasopati, Rommel Utungga (SALIENCE: English Language, Literature, and Education Journal, 2025)
This analysis looks into the expression of the unconscious mind in Liana Flores' song Rises the Moon from 2019. The study argues that the music reflects repressed emotions, desires, and psychological struggle. The song depicts a journey of emotional release and self-discovery. The authors of this essay use a qualitative method, allowing the reader to discover more about the object's background. The song reflects the idea that addressing and accepting one's unconscious creates self-awareness and personal progress, making it an effective tool for emotional healing and reflection. In conclusion, songs like Rises the Moon may not only be enjoyable in its melody, but also may contain various understandings of human psychology.